Prevalence of hypertension and prehypertension in schoolchildren from Central India - Ashish Patel; Anil Bharani; Meenakshi Sharma; Anuradha Bhagwat; Neepa Ganguli; Dharampal Singh Chouhan (Wolters Kluwer Medknow Publications, 2019)
Background: Epidemiological transition with increasing burden of cardiovascular risk factors is evident not only in adults but also in children. The data on the prevalence of prehypertension and hypertension in children show large regional differences in India and such data are not available from Central India. We, therefore, conducted a large cross-sectional study in Indore to determine the distribution of blood pressure (BP) and the prevalence of hypertension and prehypertension among schoolchildren. Methods: A total of 11,312 children (5305 girls, 6007 boys) aged 5-15 years, drawn from 80 government and private schools in equal proportion, were evaluated. Anthropometric measurements were obtained and BPs were measured using The Fourth Report on The Diagnosis, Evaluation, and Treatment of High Blood Pressure in Children and Adolescents as reference standard. BP ≥90th to <95th percentile for given percentile of height was considered as prehypertension, whereas any BP ≥95th percentile was defined as hypertension. Multiple linear regression analysis was used to find out the determinants of hypertension in these children. Results: Prehypertension was detected in 6.9% and 6.5% and hypertension was found in 6.8% and 7.0% of boys and girls, respectively. Height and weight were found to be a significant predictor of systolic and diastolic BP among both boys and girls. Conclusions: Our results show a high prevalence of prehypertension and hypertension in Indore schoolchildren with age and height being significant determinants. This highlights the need for routine BP measurements in children by pediatricians when they treat them for intercurrent illnesses or vaccinate them. It should also be mandatory as a part of school health checkup programs to detect childhood hypertension for further counseling and therapy.